Kebahagiaan Santri Pondok Pesantren Asy-Syarifah Mranggen, Keterkaitannya dengan Kemampuan Penyesuaian Diri Santri - Nisa, Fattasya Fauzun; Winta, Mulya Virgonita Iswindari; Vereswati, Hermiana (Universitas Semarang, 2023)
This research aims to determine the relationship between self-adjustment and happiness in adolescent students at the Asy-Syarifah Mranggen Islamic Boarding School. The hypothesis proposed in this research is that there is a positive relationship between self-adjustment and happiness in the students of the Asy-Syarifah Mranggen Islamic Boarding School. The more adaptive the adjustment, the higher the happiness of the students at the Asy-Syarifah Mranggen Islamic Boarding School, and vice versa. The method used in this research is a quantitative method. The characteristics of the respondents in this study were students at the Asy-Syarifah Mranggen Islamic Boarding School with an age range of 12-15 years and a maximum length of stay at the Islamic boarding school of 1 year. Data collection was carried out using the Cluster Random Sampling technique. Research data was collected using two scales, namely the Happiness Scale and the Personal Adjustment Scale. The data analysis method was carried out using Product Moment and the results of the research showed that there was a positive relationship between self-adjustment and happiness in the students of the Asy-Syarifah Mranggen Islamic Boarding School and the correlation coefficient value rᵪᵧ = 0.551 with a p value < 0.001 was obtained, so the hypothesis in this study was accepted.